Assessment of Physico-Chemical Characteristics of Lakshmipuram Lake, Anakapalli Dist., Andhra Pradesh, India - Pratap, Gudabandi Vijaya; Rao, Tulasi Bhushan; Krishna, Bellala; Lakshman, Palaka; Keerthana, Bora (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
Lakes are dynamic systems that respond to various physico-chemical characteristics. This paper deals with the physico-chemical analysis of lakshmipuram Lake of lakshmipuram village, Anakapalli Dist., Andhra Pradesh, India. This study was carried out for the period of one year (January – December 2024) to know the quality of water by examining levels of varying physio- chemical parameters such as temperature, pH, turbidity, conductance, alkalinity, DO, BOD, COD, salinity, TDS, TSS, TH, calcium, magnesium, chloride, nitrate-nitrogen, and phosphate. All the key water quality parameters are studied by following standard APHA analytical techniques. The results revealed that there was significant seasonal variation in some physico- chemical parameters and most of the parameters were in a normal range and they are present in the prescribed limits of WHO and National Lake Water Quality Criteria and Standards. It has been identified that the water is of better quality for fish farming and irrigation.